Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Unveiling buried aeolian landscapes: reconstructing a late Holocene dune environment using 3D ground‐penetrating radar - Luis Rees‐Hughes; Natasha L. M. Barlow; Adam D. Booth; Landis J. West; George Tuckwell; Tim Grossey (Journal of Quaternary Science, 2021)
Across the UK, sandy beaches and dunes protect coastal infrastructure from waves and extreme water levels during large‐scale storms, while providing important habitats and recreational opportunities. Understanding their long‐term evolution is vital in managing their condition in a changing climate. Recently, ground‐penetrating radar (GPR) methods have grown in popularity in geomorphological applications, yielding centimetre‐scale resolution images of near‐surface stratigraphy and structure, thus allowing landscape evolution to be reconstructed. Additionally, abrupt changes in palaeo‐environments can be visualized in three dimensions. Although often complemented by core data, GPR allows interpretations to be extended into areas with minimal ground‐truth control. Nonetheless, GPR data interpretation can be non‐intuitive and ambiguous, and radargrams may not initially resemble the expected subsurface geometry. Interpretation can be made yet more onerous when handling the large 3D data volumes that are facilitated with modern GPR technology. Here we describe the development of novel semi‐automated GPR feature‐extraction tools, based on ‘edge detection’ and ‘thresholding’ methods, which detect regions of increased GPR reflectivity which can be applied to aid in the reconstruction of a range Quaternary landscapes. Since reflectivity can be related to lithological and/or pore fluid changes, the 3D architecture of the palaeo‐landscape can be reconstructed from the features extracted from a geophysical dataset. We present 500 MHz GPR data collected over a buried Holocene coastal dune system in North Wales, UK, now reclaimed for use as an airfield. Core data from the site, reaching a maximum depth 2 m, suggest rapid vertical changes from sand to silty‐organic units, and GPR profiles suggest similar lateral complexity. By applying thresholding methods to GPR depth slices, these lateral complexities are effectively and automatically mapped. Furthermore, automatic extraction of the local reflection power yields a strong correlation with the depth variation of organic content, suggesting it is a cause of reflectivity contrast. GPR‐interpolated analyses away from core control thus offer a powerful proxy for parameters derived from invasive core logging. The GPR data collected at Llanbedr airfield highlight a complex dune system to a depth of 2.8 m, probably deposited in several phases over ~700 years, similar to elsewhere in North Wales.

Response to “Comment on ‘Seagrass Viviparous Propagules as a Potential Long-Distance Dispersal Mechanism’ by A. C. G. Thomson et al” - Alexandra C. G. Thomson; Paul H. York; Tim M. Smith; Craig D. H. Sherman; David J. Booth; Michael J. Keough; D. Jeff Ross; Peter I. Macreadie (Estuaries and Coasts, 2016)

The response of marine picoplankton to ocean acidification - Lindsay K. Newbold; Anna E. Oliver; Tim Booth; Bela Tiwari; Todd DeSantis; Michael Maguire; Gary Andersen; Christopher J. van der Gast; Andrew S. Whiteley (Environmental Microbiology, 2012)
Summary Since industrialization global CO 2 emissions have increased, and as a consequence oceanic pH is predicted to drop by 0.3–0.4 units before the end of the century – a process coined ‘ocean acidification’. Consequently, there is significant interest in how pH changes will affect the ocean's biota and integral processes. We investigated marine picoplankton (0.2–2 µm diameter) community response to predicted end of century CO 2 concentrations, via a ‘high‐CO 2 ’ (∼ 750 ppm) large‐volume (11 000 l) contained seawater mesocosm approach. We found little evidence of changes occurring in bacterial abundance or community composition due to elevated CO 2 under both phytoplankton pre‐bloom/bloom and post‐bloom conditions. In contrast, significant differences were observed between treatments for a number of key picoeukaryote community members. These data suggested a key outcome of ocean acidification is a more rapid exploitation of elevated CO 2 levels by photosynthetic picoeukaryotes. Thus, our study indicates the need for a more thorough understanding of picoeukaryote‐mediated carbon flow within ocean acidification experiments, both in relation to picoplankton carbon sources, sinks and transfer to higher trophic levels.

Potential for phosphonoacetate utilization by marine bacteria in temperate coastal waters - Jack A. Gilbert; Simon Thomas; Natalie A. Cooley; Anna Kulakova; Dawn Field; Tim Booth; John W. McGrath; John P. Quinn; Ian Joint (Environmental Microbiology, 2009)
Summary Phosphonates are organic compounds that contain a C–P bond and are a poorly characterized component of the marine phosphorus cycle. They may represent a potential source of bioavailable phosphorus, particularly in oligotrophic conditions. This study has investigated the distribution of the phnA gene which encodes phosphonoacetate hydrolase, the enzyme that mineralizes phosphonoacetate. Using newly designed degenerate primers targeting the phnA gene we analysed the potential for phosphonoacetate utilization in DNA and cDNA libraries constructed from a phytoplankton bloom in the Western English Channel during July 2006. Total RNA was isolated and reverse transcribed and phosphonoacetate hydrolase ( phnA ) transcripts were PCR amplified from the cDNA with the degenerate primers, cloned and sequenced. Phylogenetic analysis demonstrated considerable diversity with 14 sequence types yielding five unique phnA protein groups. We also identified 28 phnA homologues in a 454‐pyrosequencing metagenomic and metatranscriptomic study from a coastal marine mesocosm, indicating that > 3% of marine bacteria in this study contained phnA . phnA homologues were also present in a metagenomic fosmid library from this experiment. Finally, cultures of four isolates of potential coral pathogens belonging to the Vibrionaceae contained the phnA gene. In the laboratory, these isolates were able to grow with phosphonoacetate as sole P and C source. The fact that the capacity to utilize phosphonoacetate was evident in each of the three coastal environments suggests the potential for widespread utilization of this bioavailable P source.

Ground-Cover Measurements: Assessing Correlation Among Aerial and Ground-Based Methods - D. Terrance Booth; Samuel E. Cox; Tim Meikle; Hans R. Zuuring (Environmental Management, 2008)